2017
DOI: 10.1089/jop.2017.0070
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age and Initial Central Retinal Thickness on Earlier Need of Repeat Ozurdex Treatment for Macular Edema Due to Retinal Vein Occlusion: A Retrospective Case Series

Abstract: Patients receiving as-needed schedule of dexamethasone intravitreal implant had significant peak CRT and BCVA improvement. Age older than 55 years and initial CRT more than 400 μm were significant risk factors associated with repeated dexamethasone intravitreal implant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
4
11
1
Order By: Relevance
“…Moreover, the safety profile of Ozurdex for BRVO-ME demonstrated in this study was favourable and consistent with those reported in previous studies [24][25][26]. Considering the peak level, in the present study, only 24.1% of the patients ever had an IOP > 25 mmHg, and increases in IOP were generally controlled with topical medications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the safety profile of Ozurdex for BRVO-ME demonstrated in this study was favourable and consistent with those reported in previous studies [24][25][26]. Considering the peak level, in the present study, only 24.1% of the patients ever had an IOP > 25 mmHg, and increases in IOP were generally controlled with topical medications.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies had reported that older age and greater initial CRT constitute risks for Ozurdex retreatment among some populations. For example, in a previous study conducted in Taiwan of both BRVO and central RVO patients, Lin et al found that older age and greater initial CRT are risk factors for multiple injection in such patients [26]. Similarly, the COBALT study conducted in Korea also found that older age and higher initial CRT were indicators for reinjection of Ozurdex in BRVO-ME cases.…”
Section: Discussionmentioning
confidence: 95%
“…Also, some studies whose final outcome was not BCVA and CRT, the results were not reported, and patients had already received other treatments were also excluded. Finally, seven eligible studies including 393 eyes were used in the present meta-analysis [7][8][9][10][11][12]. The flow chart for the study selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Further, the CRT was disturbed by many factors, such as individual difference, measurement error, individual sensitivity to medication, and actual dosage of medication administered. The heterogeneity of mean change in the CRT after 12 months was caused by the studies of Chun-Ju Lin et al [8] and Mariacristina et al [9]. In these two studies, some patients were injected more than one time.…”
Section: Discussionmentioning
confidence: 99%
“…Younger eyes have a better visual response to the DEX treatment which is not surprising as multiple previous studies have demonstrated similar diminishment in response in older eyes. 26,27 Likely a contributing factor for the diminished response in older populations is the chronicity of their illness making it more recalcitrant to therapy.…”
Section: Uveitismentioning
confidence: 99%